Facilities Layout Analysis in a Medium-Sized Gas Turbine Manufacturing Company - Karimi, Sina (2010)
Layout design is a critical step in the process of facility planning and design. Since all performed activities are based on facilities layout, nowadays, various algorithms are in access to create a layout or to improve existing ones. These algorithms are either construction or improvement. In this essay, the layout of departments of 25MW gas turbines assembly factory was studied. Using CRAFT improver algorithm, a few changes have been suggested for the replacement of departments. The changes proposed by this algorithm result in reduction of total costs in transportation between departments by about 10 percent.